Some physiological studies on digestion in goat - Fatma Ahmed Wahba Hassan; Afaf Mohammed Azouz; Hassan Ibrahim Abass; Kamal Ali Attia (Cairo : Fatma Ahmed Wahba Hassan, 2009)
This study dealed with the effects of micro-aid ( yucca schidigera saponins ) supplementation on live body weight some ruminal parameters including ruminal protozoal and bacterial count and some blood metabolic parameters
Thesis (M.Sc.) - Cairo University - Faculty of Veterinary Medicine - Department of Animal Physiology
Issued also as CD
Keywords: Goats; Rumen; Saponins